AÇÃO HORMONAL DE ISOFLAVONAS NA PRÉ-PUBERDADE EM RATOS WISTAR COMO MODELO EXPERIMENTAL ENDÓCRINO - Sleiman, Hanan Khaled (2021)
The hypothalamic-pituitary-testicular (HHT) axis encompasses the male reproductive system, which during fetal life is developed and in postnatal life undergoes sexual differentiation in the brain. Phytoestrogens are substances that occur naturally in vegetables and have biological functions in relation to them. Soy is a food widely consumed by the population and in its composition is isoflavone, a flavonoid, which has the following main bioforms: genistein, daizein, glycitein and equol, found in the form of aglycone or glycosides. Despite the beneficial effects of isoflavones, such as herbal medicines used to improve postmenopausal symptoms, antioxidants, acting in the prevention of diseases related to the heart and osteoporosis, studies show that it can act as an endocrine disruptor. The endocrine disrupting effect damages human health, acting on any part of the endocrine system by blocking or mimicking the action of naturally produced hormones. Isoflavones, as they present a chemical structure similar to 17β-estradiol, a naturally produced estrogen, compete for the same binding site as estrogen receptors. The objective of this study was to evaluate whether exposure to isoflavones, during the sexual differentiation window (critical phase of development), causes changes in the HHT axis. Newly weaned prepubertal Wistar rats were treated with three different concentrations of isoflavone: 0.5 mg /Kg; 5 mg /Kg; 50 mg /Kg. In addition to these three treatment groups, a control group treated with corn oil diluent was also used. All animals received their corresponding doses daily through gavage (forced ingestion by tube) in the morning, after weighing. Treatment started at PND 23 and ended at PND 60. The evolution of age and weight at puberty was assessed daily. At the end of the experiment, the animals were euthanized under general anesthesia, cardiac puncture and beheading. The tissues were collected for further analysis. The blood was collected for hormonal analyzes of testosterone, estradiol, LH and FSH. The testicles, epididymides and seminal vesicle were removed for weighing, evaluation of sperm production and integrity, evaluation of the integrity of the acrosome, evaluation of mitochondrial activity and sperm morphology. One of the testicles was used to identify alterations in gene expression, which participate in the regulation of spermatogenesis, through real-time quantitative PCR (RT-qPCR). The data obtained were performed using the software Statistica 7.0, Statsoft Inc. Statistical differences were considered when p <0.05. Exposure to isoflavones in the prepubertal age did not change the weight at puberty of the animals, nor did it change the weight of dependent androgen tissues, but there was a delay in age at puberty in the treated groups 0.05 mg / kg and 5 mg / kg. It was observed that the total sperm production / testis was reduced in the treated group by 0.5 mg / kg, since when the total sperm production / gram testis is evaluated, there are no significant differences. When the daily sperm production / testicle was evaluated, the animals treated 0.5 mg / kg and 50 mg / kg showed a reduction in this parameter, whereas when the daily sperm production / gram testicle was evaluated, there were no significant differences. Regarding the sperm reserve in the epididymis, in the three treated groups there was less sperm concentration. The sperm transit time in the epididymis was affected in the tail portion of the treated animals 5 mg / kg, where a faster passage of the seminal fluid occurs. The integrity of the acrosome and the integrity of the plasma membrane of the sperm was affected in all treated groups, indicating lower sperm fertilization capacity, reduced fertility and shorter survival. Mitochondrial activity, related to motility, was reduced in the treated groups 0.5 mg / kg and 50 mg / kg, as well as their structure and functionality, assessed by sperm pathology. In gene expression, there were no results with significant differences. In the hormonal profile of testosterone and estradiol, both presented a reduction in the treated groups of 0.5 mg / kg and 5 mg / kg. FSH was increased in the treated group 0.5 mg / kg and LH in the treated groups 5 mg / kg and 50 mg / kg. These results demonstrate that the exposure to isoflavones during the critical period of sexual differentiation, modifies the activity of the hypothalamic-pituitary-testicular axis, which has negative consequences on the reproduction of animals when they are adults.